2021
DOI: 10.21595/jmeacs.2021.21868
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the SCM structure parameters on the engine vibration and optimization the engine power

Abstract: In this paper, based on the slider-crank-mechanism (SCM) dynamics model, the dynamic parameters of the engine including the eccentricity () between crankshaft centre and cylinder centre of the SCM, the length and radius of the connecting rod and crankshaft, and engine speed are researched on the engine vibration and power, respectively. The dynamic parameters are then optimized based on the multi-objective genetic algorithm developed in MATLAB software to improve the vibration and power of the engine. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…To determine the vibration excitation source of the engine, the gas pressure 𝑃 in a cylinder measured based on the experiment result at 2000 rpm of an engine in Ref. [10][11], as shown in Fig. 3(a), is used to calculate the impacting forces of 𝐹 and 𝐹 .…”
Section: The Vibration Excitation Of the Enginementioning
confidence: 99%
See 1 more Smart Citation
“…To determine the vibration excitation source of the engine, the gas pressure 𝑃 in a cylinder measured based on the experiment result at 2000 rpm of an engine in Ref. [10][11], as shown in Fig. 3(a), is used to calculate the impacting forces of 𝐹 and 𝐹 .…”
Section: The Vibration Excitation Of the Enginementioning
confidence: 99%
“…The vibration studies on internal combustion engines showed that, in the low frequency regions of the engine below 100 Hz, the acceleration response of the engine was relatively high [9][10][11], and it also significantly affected the ride comfort of vehicles when the engine's vibration excitation was combined with the vibration excitation from the rough road surface. Besides, the existed studies had also shown that the engine isolation system mainly used by the traditional rubber mount (TRM) had not yet been effective enough in isolating vibrations of the engine.…”
Section: Introductionmentioning
confidence: 99%